Experimental investigation on gripper force of electrically activated non-contact swirl vane gripper. (2021) - Rahul, M.; Sivapirakasam, S.P.; Vishnu, B.R.; Aravind, S.L.; Mohan, Sreejith
Abstract: This research work evaluates, Suction Force, Stable levitation region, and clearance distance for evaluating the performance of the swirl vane gripper. The Swirl vane gripper is nothing but a new non-contact gripper that uses negative pressure created by the air swirling flow to create an upward-lifting force. The variation of the suggested parameters with motor speeds (1000 rpm to 20, 000 rpm) was studied. From the F-h curve (i.e., suction force versus distance between the work piece and the gripper), stable levitation region of the gripper was obtained. Different clearance distances were set and the gripper was actuated at these clearance distances and the effect of clearance distance on maximum suction force was studied. It was found that the gripper can be used successfully to grip 2–4 in. silicon wafers. One of the main limitations, which was found to be in the gripper was that, vibration levels were high at an rpm of 18, 000 and above. The variation of energy consumption of the developed gripper with lifting force was determined and electrical energy consumption (in Watts) versus lifting force was plotted. The experimental results were then compared with that of Bernoulli and Vortex gripper and the energy consumption was found to be 95.82% less for swirl vane gripper with the Bernoulli gripper and 92.24% less than that of vortex gripper.